ANALISIS PERUBAHAN INDEKS KERAPATAN VEGETASI MEMANFAATKAN CITRA LANDSAT (Studi Kasus : Provinsi DKI Jakarta) - Aditya Khairawan, (2020)
The development of the city causes changes in land cover including a reduction in vegetated land. Information on vegetation density is important for regional planning related to environmental quality. This study aims to analyze the vegetation density index in DKI Jakarta in 2013 and 2018 and to analyze changes in density between these years. In this study, the methods used are NDVI (Normalized Difference Vegetation Index) and Maximum Likelihood. The vegetation density index is classified into 4, namely: nonvegetation, low, medium, and high, while land cover is classified into 6, namely: water bodies, clouds, green open space (RTH), built land, and open land. Based on field checks, the results of the NDVI method truth test or accuracy were 87.82% in the 2013 image and 86.72% in the 2018 image. The land cover accuracy in the 2013 image was 74.79% and the 2018 image was 75.41%. The NDVI method is quite good in measuring the density level of vegetation in an area.